The encyclopedia of leadership a practical guide to popular leadership theories and techniques - Hiebert, Murray 1943- (Gale virtual reference library, 2001)
Comprehensive reference guide to over 200 of the most important business leadership principles, theories, tools, and techniques. Each entry features a brief, one-page summary of an influential theory or tool, followed by a worksheet or exercise. A comprehensive guide to the leadership principles, theories, tools and techniques in the organizational world. It helps to find brief summaries of various important leadership ideas including: the basic competencies and practices of successful leaders; finding the best leadership technique for the situation; and, leading groups and teams.